Smoking and Breast Cancer - Reynolds, Peggy (Journal of mammary gland biology and neoplasia, 2013)
The potential role of smoking in breast cancer risk has been the subject of over 100 publications, numerous scientific reviews, and animated debate. Tobacco exposure is a well-established cause of lung cancer, and is thought to account for nearly one third of all cancer deaths. Tobacco smoke contains thousands of chemicals, many of which are known to be mammary carcinogens. Although not initially thought to be a tobacco-related cancer, over the last several decades evidence has been accumulating on the role of both active smoking and secondhand smoking in the etiology of breast cancer. The human health evidence has been systematically evaluated not only by several independent researchers but also by several expert agency panels including those of the U.S. Surgeon General, the International Agency for Research on Cancer, the California Environmental Protection Agency, and a coalition of Canadian health agencies. Although the assessments have varied with time and across reviewers, the most recent weight of the evidence has suggested a potentially casual role for active smoking and breast cancer, particularly for long-term heavy smoking and smoking initiation at an early age. The role of secondhand smoking and breast cancer is less clear, although there has been some suggestion for an increased risk for premenopausal breast cancer. Recent studies evaluating the possible modifying role of polymorphisms in genes involved in the metabolism of tobacco products, particularly NAT2 , have contributed another dimension to these assessments, although to date that evidence remains equivocal.